2020
DOI: 10.1136/jitc-2020-000798
|View full text |Cite|
|
Sign up to set email alerts
|

Apatinib plus camrelizumab (anti-PD1 therapy, SHR-1210) for advanced osteosarcoma (APFAO) progressing after chemotherapy: a single-arm, open-label, phase 2 trial

Abstract: BackgroundResults of our previous study showed high objective response but short-term activity of apatinib in advanced osteosarcoma. We aimed to investigate the activity of apatinib in combination with camrelizumab in patients with inoperable high-grade osteosarcoma progressing after chemotherapy.MethodsThis open-label, phase 2 trial was conducted at Peking University People’s Hospital. We enrolled patients with advanced osteosarcoma progressed after chemotherapy. Patients received 500 mg apatinib orally once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 29 publications
3
107
0
Order By: Relevance
“…It is important to identify patients who may benefit from this treatment strategy. [ 9 , 11 , 26 ] Therefore, we used three methods to evaluate the relationship between IRGP signature and immunotherapy efficiency. First, we found that IRGP signatures can predict the outcome of patients with metastatic melanoma who received anti-PD-L1 treatment and that patients with poor treatment response showed an increasing trend in IRGP signature values.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify patients who may benefit from this treatment strategy. [ 9 , 11 , 26 ] Therefore, we used three methods to evaluate the relationship between IRGP signature and immunotherapy efficiency. First, we found that IRGP signatures can predict the outcome of patients with metastatic melanoma who received anti-PD-L1 treatment and that patients with poor treatment response showed an increasing trend in IRGP signature values.…”
Section: Discussionmentioning
confidence: 99%
“…The single-arm, phase II trial (NCT03359018) [ 43 ] investigated the synergistic effect of TKIs in combination with ICIs in chemotherapy refractory osteosarcomas. Studies have shown that expression of PD-L1 associates significantly with the presence of T-cells and dendritic cells in the tumor, but also with a poorer five-year event free survival in patients with osteosarcoma [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SARC028 clinical trial (NCT02301039) [ 18 ] showed PD-L1 expression in UPS cells, corresponding with an OR after treatment with ICI monotherapy. Moreover, apatinib combined with pembrolizumab in osteosarcomas (NCT03359018) [ 43 ] showed that tumors with PD-L1 ≥ 5% correlated significantly with PFS. On the other hand, axitinib in combination with pembrolizumab (NCT02636725) [ 38 ] showed PD-L1 expression in all patients with ASPS, but no correlation with PFS for more than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a trial of pembrolizumab in patients with advanced sarcoma (SARC028; NCT identifier: NCT02301039), one of the 22 patients in the osteosarcoma arm that were given pembrolizumab demonstrated an objective response [ 105 ]. A trial of camrelizumab in combination with apatinib in osteosarcoma also seemed to slightly prolong progression-free survival, though the response rate to these therapies is as of yet not optimized [ 106 ].…”
Section: Treatment Strategies and Molecular Targetsmentioning
confidence: 99%